Frequency of Physical Activity-Related Injuries Among Adolescents: An Umbrella Review - Kerttu Toivo; Peter Bakalár; Mari Leppänen; Jari Parkkari; Jari Parkkari; Ensar Abazović; Boštjan Šimunič; Kaja Teraž; Kaja Teraž; Marta Malinowska-Cieślik; Jaroslava Kopčáková; Aurel Zelko; et al. (Public Health Reviews)
ObjectivesThe aim of this umbrella review was to investigate the frequency of physical activity-related injuries (PARI) among adolescents. Our secondary objective was to describe the available reviews of injuries in three settings: organized sports, leisure time physical activity (PA), and school physical education (PE).MethodsWe conducted an overview of reviews consistent with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines on the frequency of physical activity related injuries in adolescents.ResultsWe identified 19 systematic reviews with at least moderate quality to include in the review. We were not able to pool data from reviews and conduct meta-analysis due to heterogeneity of injury definitions, exposure times, and sample demographics. All reviews included studies of injuries sustained in organized sports, and injury incidence was higher during matches than training. No systematic reviews were found focusing on leisure time or school-based PA injuries.ConclusionHigh-quality research is essential to understand the frequency of various types of physical activity related injuries among adolescents in organized sports, PE, and leisure time activities to develop more effective prevention strategies.